Karakteristik Mikrobiologi dan Kimia Susu Kefir dari Susu Biji Lotus (Nolumbo nucifera) - Zubai Zubai; Ace Baehaki; Rinto Rinto; Sherly Ridhowati Nata Iman; Muhammad Hendri (Universitas Sriwijaya, 2022)
This sudy aims to determine the effect of increasing of the concentration of lotus milk on the chemical and microbiological properties of kefir milk. This research method using a Randomized Block Design (RBD) with different treatment concentration lotus milk with 5 levels of treatment (A0 100 % cow’s milk and 0 % lotus seed milk, A1 75 % cow’s milk and 25 % lotus seed milk, A2 50 % cow’s milk and 50% lotus seed milk, A3 25 % cow’s milk and 75% lotus seed milk, A4 0 % cow’s milk and 100% lotus seed milk) and repeated 3 times. The treatment parameters observed included chemical analysis (total lactic acid, total alcohol an pH) and microbiological analysis (total lactic acid bacteria). The result showed that the addition of the concentration of lotus milk and cow’s milk in making kefir had a significant effect on the value of the degree of acidity, total lactic acid, total alcohol and total lactic acid bacteria. The value of the degree of acidity ranges from (3.57-3.99), the total lactic acid ranges from (0.52-1.04%), the total alcohol ranges from (0.56-1.10%) and the total lactic acid bacteria ranges from (8.52-8.60 Log cfu/ml).